Environmental and Disaster Risk Reduction literacy among Senior High School students in Sibagat Agusan del Sur - Bernal, Analyn; Apdohan, Julie Rose (Amcolabora, 2023)
Abstract. The study aimed to determine the level of environmental and disaster risk reduction literacy among Senior High School students in Sibagat, Agusan del Sur, Philippines. The study utilized a modified questionnaire to collect data from various Senior High School strands. The study found that social media was the most used source of information on environmental and disaster risk reduction. Earthquakes and floods were the most experienced hazards, with early evacuation as the most popular coping strategy. Students possessed high levels of awareness on environmental issues contributing to disaster risk and high level of practices towards disaster risk reduction. The study has significant differences in both awareness and practices among different senior high school strands. The level of practice strongly and positively correlates with the level of awareness. The Science Technology Engineering and Mathematics (STEM) strand had the highest mean score for awareness and the Agricultural crop production strand had the highest mean score for practices toward disaster risk reduction. The study found a negative correlation between awareness on environmental issues and Electrical Installation and maintenance (EIM) strand. Conversely, practices towards disaster risk reduction exhibited strong positive correlation with agricultural strand while demonstrating a strong negative correlation with EIM strand and both correlations were statistically significant. The study recommends prioritizing the promotion of environmental and disaster risk reduction literacy among secondary school students by incorporating the topic into the school curriculum, reinforcing related programs and activities, and institutionalizing eco-movement through student organizations. Keywords: Environmental literacy, Disaster Risk Reduction literacy, Sibagat Agusan del Sur, Philippines